Synthesis and Characterization of Some New Di-amines Derived from Di-amines Supplemented with Di-heterocyclic Five Membered Rings and Some Aromatic Aldehydes - Noor S. Noori (Journal of Global Pharma Technology, 2016)
It has been documented that imines and heterocyclic compounds with five membered rings and their derivatives, have enormous biological activity in various area as medicinal and pharmaceutical. Therefore, supplementing the di imines with five -membered heterocyclic rings, perhaps enhance the biological activity characters of the resulting products. Consequently, the target of present work involve the developing of new imines derived from selected di amines after connecting a five membered heterocyclic rings of the type di thiazole and di oxazole to the parent molecules via the reaction of the previous di amines with chloroacetyl chloride yield the corresponding amides [A1-A3] , then subsequent reaction of the later with of thiourea and urea give substantially new di thiazol [th1-th3] and di oxazole [Ox1-Ox3] respectively .Reaction of these new developed di amines with selected aromatic aldehydes result a pavantly in the formation of the desired bis imines [Sc1-Sc10]. On the other hand the structures of all the synthesized compounds were confirmed by their physical properties, such as colors and melting points and spectroscopic measurements FT-IR, 1H-NMR and 13C-NMR for selected compounds.Keywords: Di imines, Chloroacetyl chloride, Thiazole-2, 4-diamines, oxazole-2, 4-diamines.